Critical narratives of multiethnic women focusing on their indigenous ethnicity: navigating the schooling system from early childhood through master's and beyond - Chacon, Phyllis, author; Timpson, William, advisor; Anderson, Sharon, committee member; Banning, James, committee member; Bubar, Roe, committee member (Colorado State University. Libraries, 2015)
This qualitative inquiry into the completion of a Masters and or Doctorate degree by Native American women is the result of 25 years as a student and professional in the field of education. Within a nation that claims to provide an equal and fair education for all its citizens, the stark underrepresentation of indigenous women in higher education is a topic that needs to be reconciled. This study examined the lives of four multiethnic Native women who obtained advanced degrees. The study examined the lives of Native women who have been scattered across the land. Today, many indigenous women are multiethnic living in two cultures. Many have held on to their birthright and cultures while adapting and persevering into the dominant culture. Nine themes emerged from interviewing the four women for this study: (1) self-determination, (2) cultural oppression, (3) racial/ethnic identity (4) social environment/economics, (5) marginalization, (6) violence, (7) love of learning, (8) family systems, and (9) educational systems. Recommendations for further graduate inquiry based on the schooling of Native women include: 1. Expand the study to Native women being educated on the reservation vs. Native women being educated in suburban and urban schools during their K though 12th grade education. 2. A qualitative and quantitative study on measurements of services; tools such as computers, support programs, gaps in test scores and graduation rates.
Keywords: cultural oppression; love of learning; marginalization; racial/ethnic identity; self-determination; violence